Dendritic Cells: A Double-Edged Sword in Immune Responses during Chagas Disease - Gil-Jaramillo, Natalia; Motta, Flávia N.; Favali, Cecília B. F.; Bastos, Izabela M. D.; Santana, Jaime M. (Frontiers in Microbiology, 2016)
Dendritic cells (DCs) are the most important member of the antigen presenting cells (APC) group due to their ability to recognize antigen at the infection site and their high specialized antigen internalization capacity. These cells have central role in connecting the innate and adaptive immune responses against Trypanosoma cruzi, the causative agent of Chagas disease. These first line defense cells modulate host immune response depending on type, maturation level, cytokine milieu and DC receptor involved in the interactions with T. cruzi, influencing the development of the disease clinic forms. Here, we present a review of DCs–T. cruzi interactions both in human and murine models, pointing out the parasite ability to manipulate DCs activity for the purpose of evading innate immune response and assuring its own survival and persistence.